Self-assembly between dicarboxylate ions and a binuclear europium complex: formation of stable adducts and heterometallic lanthanide complexes. - Tilney, J; Sørensen, T; Burton-Pye, B; Faulkner, S (2011)
A binuclear lanthanide complex consisting of two lanthanide binding domains linked by a m-xylyl bridging unit forms very stable 1 : 1 adducts with benzene dicarboxylic acids and their derivatives. The complex with isophthalate derivatives is particularly stable.